System Diagnostics of the Social Comfort of Living in the Region: Methodological Approach and the Results of Assessment - Bakanach, Olga V.; Proskurina, Natalya V.; Sazhin, Yuri V.; Skvortsova, Marina A. (International Journal of Economics and Financial Issues, 2016)
The article suggests methodological approach to determining the level of social comfort of living of the population in the regions of Povolzhskiy Federal District (PFD). In order to provide better perception of the analysis there was built the cardiogram of the differences in the level of social comfort for the regions of PFD on the basis of modern GIS-technologies. According to the described methodology the methodical apparatus was suggested which is based on indicative analysis using natural assessments of the object (indicators). The structure of the system of indicators modeling the state and development of social comfort of living in the region is given. On the example of the Republic of Mordovia there was performed multivariate modeling of social comfort of living of the population. The modeling was made in three ways: by constructing an integral index based on the subjective evaluation of the region’s residents, by combining subjective and objective information into a single indicator of social comfort of living of the population. Finally, we analyzed the dynamics of the level of social comfort of living of the population of the Republic of Mordovia in 1994-2013. Keywords: Anamorphosis; Discomfort; Indicator; Indicative analysis; Modeling; Social comfort JEL Classifications: Ð¡19; Ð¡33